Cross‐cultural comparison of seven morningness and sleep–wake measures from Germany, India and Slovakia. (30th August 2014) - Randler, Christoph; Prokop, Pavol; Sahu, Subhashis; Haldar, Prasun
<x xml:space="preserve">Abstract</x> Morningness–eveningness or circadian typology can be viewed as an interesting aspect of individual differences. Morningness–eveningness is a preference for a given time of day for physical or mental performance, but also reflects aspects of affect. Here, we used seven different measures to assess differences in morningness–eveningness between Germany, Slovakia and India. The hypothesis was that Indians should be earliest chronotypes, followed by Slovakia and then Germany, because of higher temperatures in India, and the fact that Slovakia is located farther east compared to Germany. We applied the Composite Scale of Morningness (CSM), the Circadian Energy Scale (CIRENS), the CAEN Chronotype Questionnaire (CCQ), and habitual sleep–wake variables to calculate sleep duration, midpoint of sleep and social jetlag. Sample sizes were N = 300 (Germany), N = 482 (Slovakia) and N = 409 (India). Country had the strongest influence on morningness–eveningness. Germans were latest chronotypes and differed in all seven measures from Indians but differed from Slovakians only in the energy level at the evening and midpoint of sleep. Slovakians and Indians differed in all measures but the energy level (CIRENS). Women scored higher on the CSM, lower on CIRENS, lower on the morningness–eveningness (ME) scale, but higher on distinctness (DI) scale. Women slept longer and had an earlier midpoint of sleep.